In Situ I-V Measurements of Ultraviolet Enhanced ZnS:TiO2/ITO Quantum Dots Hetero-Junction Photodiode under 120 MeV Au9+ Ions - Sana1, Prabha; Verma2, Shammi; Malik3, M.M. (Asian Journal of Chemistry, 2013)
This work reports the development of ZnS:TiO2/ITO heterojunction structure by deposition of colloidal ZnS/TiO2 quantum dots (QD's) on indium tin oxide (ITO) coated glass plate. To study the present quantum dots based heterojunction photodiode performance under harsh radiation atmosphere, its in situ current-voltage (I-V) characteristics has been studied by the irradiation of 120 MeV Au9+ ions at different ions fluences. The I-V analysis shows the variations in the parameters values, resulted by the production of more defects at the interface of heterojunction by 120 MeV Au9+ ions. Moreover the XRD analysis shows the structural modification under the swift heavy ions, resulted by defect production. The ultraviolet (376 nm) photo detection characteristic of present quantum dots heterojunction has been enhanced after the swift heavy ions irradiation.